Perhitungan Efisiensi Perpindahan Panas pada Unit Cooler Di PT. XY - Ratna Kristina Tarigan (JURNAL VOKASI TEKNIK, 2023)
PT. XY Medan is a company engaged in the production of NPK fertilizer. One of its products is NPK fertilizer with the formulation 12:12:17:2, which contains 12% nitrogen (N) from urea, 12% phosphorus (P2O5), 17% potassium (KCl), and 2% magnesium (MgO). One of the main stages in the production process is cooling, which is carried out using a rotary cooler operating at a rotational speed of 7 rpm and an inclination angle of 2°. The cooling medium is ambient air drawn into the rotary cooler by an exhaust fan. Heat transfer efficiency is an important parameter because insufficient or excessive cooling may affect the quality of the NPK fertilizer. In addition, evaluating heat transfer efficiency is necessary to determine whether the cooling equipment operates efficiently or requires process optimization. The average residence time of the fertilizer in the rotary cooler is 10 minutes. The average inlet temperature of the NPK fertilizer is 66.8 °C with a mass flow rate of 6,000 kg/h, while the average inlet air temperature is 34 °C with an average air flow rate of 12,626.6132 kg/h. The calculation results show that the average heat released by the NPK fertilizer during the cooling process is 28,478.9244 kcal/h, whereas the average heat absorbed by the cooling air is 26,332.98 kcal/h. Consequently, the average heat transfer efficiency of the rotary cooler is 82.09%. The maximum allowable moisture content of NPK fertilizer with the 12:12:17:2 formulation is 2%, while the average final moisture content obtained at the end of the process is 1.444%, indicating that the product meets the required quality standard.